Analisis Eksperimental Dampak Pemasangan Bracing Pada Struktur SDOF Dan MDOF Terhadap Beban Getar Horizontal - Tauladan, Muhammad Wafiq; Monica MG, Intan; Suryanita, Reni (Jurnal Bangunan, Konstruksi & Desain, 2025)
Buildings subjected to horizontal vibration loading can cause displacement deformation and even collapse. Laboratory-scale testing to simulate vibrations due to horizontal loading can be done using structural modeling using a shaking table as the vibration source medium. This can be done because large-scale testing is very difficult to do due to cost and time constraints. This study aims to analyze the impact of bracing use on the response of Single Degree of Freedom (SDOF) and Multi Degree of Freedom (MDOF) structures due to horizontal vibration loads. The building models tested were one to three-story models with and without bracing. Testing was carried out using a one-way horizontal shaking table with varying frequencies of 15 Hz, 20 Hz, and 25 Hz to see the differences in each structural response. The parameters observed in this study were model displacement and acceleration. The study results show that the model without bracing experiences a maximum acceleration at each vibration table frequency of 490 cm/s2 with a vibration table frequency of 15 Hz, 649 cm/s2 with a vibration table frequency of 20 Hz, and 774 cm/s2 with a vibration table frequency of 25 Hz. Meanwhile, the model using bracing experiences the largest acceleration reduction of up to 35% for a vibration table frequency of 25 Hz. Bracing increases the lateral stiffness of the structure thereby reducing deformation to be smaller than the structure without bracing. The maximum displacement value of the model without bracing at each frequency is 1.08 cm at a vibration table frequency of 15 Hz, 1.54 cm at a vibration table frequency of 20 Hz, and 2.84 cm at a vibration table frequency of 25 Hz. From the study conducted, it can be concluded that the use of bracing in SDOF and MDOF structures has a reduction in structural response of up to 35%.